Small Business and International Entrepreneurship - Radchenko, Anastasiia; Pichanič, Mikuláš, 1942-; Staňková, Lenka; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
Small and medium-sized enterprises together with start-ups are highly important in the nowadays economic environment. Such companies contribute raise of employment, stimulate the economic growth and innovation development. However, not all start-ups can survive more than five-year period. Support from government and private investors can help to overcome such problems. Moreover, SMEs internationalization and global functioning can support businesses during the tough times. The goal of the Master thesis is to analyze business environment for SMEs on the EU scale and to identify the opportunities and borders faced by SMEs. A more in-depth analysis is conducted on the example of three countries: Czech Republic, Germany and Italy. In order to get better picture of start-up procedures and companys operation, the example of business plan analyses for micro business is provided.
Vedoucí práce: Mikuláš Pichanič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses